Etika Auditor Sebagai Pemoderasi Pengaruh Kompetensi dan Tekanan Anggaran Waktu Terhadap Kualitas Audit - Gea, Fabian; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2018)
Financial statements user especially shareholders will make decisions based on reports that have been endorsed by the auditor. This explains the important role of auditors in ensuring the high quality of a company's financial statements. The purpose of this study is determine the effect of auditor ethics as a moderator of the influence of competence and time budget pressure on audit quality in Bali Province. Data collected through form a questionnaires that distributed directly to auditors who work in Public Accounting Firm in Bali. The population in this study were all auditors working on KAP in Bali Province with the quanitity of auditors as much as 43 auditors with saturated sampling method, while the analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and hypothesis testing, it can be concluded that (1) the competence has a positive effect on the quality of audit, (2) the time budget pressure negatively affect the audit quality, (3) the auditor ethics strengthens the competence relation on audit quality, (4) the relationship of time budget pressure to audit quality. Keywords: audit quality, auditor ethics, competence, time budget pressure.